Acessibilidade física na ufpa: diretrizes urbanas para deslocamentos pedonais acessíveis - SILVA, Rafael William Souza da (2019)
A segment of simple building blocks set up in large lands far from urban centers, beneath a zoning that abruptly separated teaching from research, theory from practice, and graduate from undergraduate. In Brazil, college campuses have characteristics that reflect the ideals of education and development in their time of construction, but they have produced consequences for mobility into the campus, land use, and infrastructure. Down the current effort for an inclusive education and inclusive society as a whole, the model undertaken in these college campuses proves to be insufficient. The campus José da Silveira Netto, head office of the Federal University of Pará in Belém, northern Brazil, is an example of this dissonance. Even with a promotion of road infrastructure improvements in recent years, it occurs that such efforts do not completely address the issue of accessibility by not enclosing a practice of urban planning, design and management. Due to this issue, it will be drawn up studies about walkways and sidewalks network and land uses at the campus, as well as bibliographic research and data collection, which aim to produce a guideline for pedestrian accessibility in order to be discussed and implemented by the University.